2001
DOI: 10.1107/s0108768101002737
|View full text |Cite
|
Sign up to set email alerts
|

Dipyrimidine–copper(II) dinitrate complexes showing magnetic interactions

Abstract: Crystals of Cu(II)(NO(3))(2)(pm)(3) (1), and two crystalline forms of Cu(II)(NO(3))(2)(H(2)O)(2)(pm)(2), (2) and (3), showed ferromagnetic, antiferromagnetic and paramagnetic interactions at extremely low temperatures, respectively. Crystal structure analyses revealed that the complexes were catena-dinitrato[mu-pyrimidine-kappaN(1):kappaN(3)]-(pyrimidine-N(1))copper(II), [Cu(NO(3))(2)(pm)(2)](n), catena-diaquadinitrato[mu-pyrimidine-kappaN(1):kappaN(3)]copper(II), [Cu(NO(3))(2)(H(2)O)(2)(pm)](n), and diaquadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 18 publications
3
28
0
Order By: Relevance
“…Each metal node is connected to six adjacent nodes within the sheet using a total of eight hydrogen bonds, utilising all four water hydrogen atoms (two for each H 2 O), and both coordinated NO 3 -anions participating in two hydrogen bonds each. These hydrogen-bonded sheets are then crosslinked by the pyrimidine ligands into a three-dimensional network of 3 6 .4 18 .5 3 .6 topology ( Figure 4). A single-crystal diffraction study of 5 revealed a highly related structure to that observed in 1-4.…”
Section: Resultsmentioning
confidence: 99%
“…Each metal node is connected to six adjacent nodes within the sheet using a total of eight hydrogen bonds, utilising all four water hydrogen atoms (two for each H 2 O), and both coordinated NO 3 -anions participating in two hydrogen bonds each. These hydrogen-bonded sheets are then crosslinked by the pyrimidine ligands into a three-dimensional network of 3 6 .4 18 .5 3 .6 topology ( Figure 4). A single-crystal diffraction study of 5 revealed a highly related structure to that observed in 1-4.…”
Section: Resultsmentioning
confidence: 99%
“…The apical positions of the octahedral coordination polyhedron are occupied by the N of a AMPY molecule (the Cu1 -N1 distance being 2.2724(18) Å and the Cu atom of the dimer). The Cu-N ax distance in unsubstituted pyrimidine containing copper complexes lies in range of (2.033 (4) Å and 2.025 (4) Å) [29,30]. The copper atoms are displaced from the respective basal planes towards the apical nitrogen atoms by 0.176 Å, and the Cu–Cu separation within the dimer was found to be 2.6691(5) Å, is typical for the dinuclear paddle wheel type of copper coordination compounds.…”
Section: Resultsmentioning
confidence: 99%
“…The above given examples indicate that the concept of spin polarization, which almost always works in organic chemistry to predict ferromagnetic interactions and to rationally develop new high-spin compounds, cannot be applied in a straight-forward manner to transition metal complexes. Several theoretical investigations were performed to get insight into the question why the concept of spinpolarization cannot be applied that simply to transition metal complexes [63,67,92,93]. Karafiloglou already showed for organic diradicals that not only the spin polarization, but also exchange and superexchange interactions contribute to the overall coupling [56].…”
Section: Applications Of the Spin-polarization Mechanism To Transitiomentioning
confidence: 99%